THE MAIN DIRECTIONS OF MARKETING ACTIVITIES IN ENTREPRENEURSHIP - Dilafiruz Narzieva (The Conference Hub, 2025)
This article presents the importance of marketing in improving the efficiency of entrepreneurial activity in a market economy, analysis of marketing decision-making in entrepreneurial activity, and the main areas of marketing.
Keywords: Marketing, social media marketing (SMM), email marketing, digital marketing, entrepreneurship.